2013
DOI: 10.1590/1679-775720130255
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive bonding of resin composite to various titanium surfaces using different metal conditioners and a surface modification system

Abstract: ObjectiveThis study evaluated the effect of three metal conditioners on the shear bond strength (SBS) of a prosthetic composite material to cpTi grade I having three surface treatments. Material and MethodsOne hundred sixty eight rivet-shaped specimens (8.0x2.0 mm) were cast and subjected to polishing (P) or sandblasting with either 50 mm (50SB) or 250 mm (250SB) Al2O3. The metal conditioners Metal Photo Primer (MPP), Cesead II Opaque Primer (OP), Targis Link (TL), and one surface modification system Siloc (S)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…The results observed in this group are in agreement with similar studies, which concluded that sandblasting and primer application significantly improved the SBS of the resin cement to titanium. [ 17 18 19 20 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…The results observed in this group are in agreement with similar studies, which concluded that sandblasting and primer application significantly improved the SBS of the resin cement to titanium. [ 17 18 19 20 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…The increase in seating force might also lead to a possible reduction in cement film thickness depending on the composition and alter the cohesive strength of the self-adhesive resin cement because it is reported that self-adhesive resin cements exhibit lower mechanical properties than conventional resin cements. 37 Although resin cements containing phosphoric groups are able to produce strong chemical bonds with the superficial oxide layer of titanium, 38 the decrease in SBS value of RXU/CP Ti factor level combination under 50 N seating force might be due to this decrease in the cohesive strength and surface wettability of the RXU. 32 33 34 35 36 37 38 39 Also, the glass-ionomer cement establishes no chemical bond with noble metal alloys.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesive, mixed or cohesive failure modes were assigned, according to proportion of resin composite cement (or resin) remained on the Ti surface. When ≤33% resin cement remained on Ti substrate, it was considered adhesive failure; when ≥34% but ≤66%, mixed failure mode, whereas ≥67% and ≤100% was considered cohesive failure 16) .…”
Section: Failure Mode Analysismentioning
confidence: 99%